SUSTAINABILITY ACTVITIES CSR ON SOCIAL MEDIA AND ENGAGING STAKEHOLDERS : CONSUMER PERSPECTIVE - Ayu Lestari; Moch. Doddy Areifianto (Universitas Islam Negeri Alauddin Makassar, 2022)
CSR activities through social media is one of the media that is currently widely used which involves the company's stakeholders will have an impact that changes the way of communicating and builds the company's reputation. The purpose of this study is to investigate the impact of CSR on social media by involving engaging stakeholders, brand image, electronic word of mouth (E-WOM) and future purchase intention. The research method used is quantitative method with descriptive analysis data analysis technique using the AMOS Structural Equal Model (SEM). The sample used in this study was 395 samples of social media users in JABODETABEK. The results obtained in this study are eganging stakeholders, brand image and electronic word of mouth (E-WOM) have a significant positive effect on CSR activities in social media. In addition, brand image, electronic word of mouth (E-WOM) has a significant positive effect on future purchases. As well as brand image mediating between CSR activities on social media has a positive effect on E-WOM and future purchases.